2023
DOI: 10.1038/s41598-023-33187-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Lassa fever diagnosis in suspected cases reporting to health facilities in Nigeria

Abstract: Lassa fever (LF) remains endemic in Nigeria with the country reporting the highest incidence and mortality globally. Recent national data suggests increasing incidence and expanding geographic spread. Predictors of LF case positivity in Nigeria have been sparsely studied. We thus sought to determine the sociodemographic and clinical determinants of LF positivity amongst suspected cases presenting to health facilities from 2018 to 2021. A secondary analysis of the national LF surveillance data between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This difference could be due to variations in occupation, exposure to rodents, or differences in immune responses. Studies have shown that males, especially farmers and hunters, are more likely to be exposed to rodents [22,23]. Genetic, hormonal, and behavioral factors may also contribute to varying susceptibility between males and females [24].…”
Section: Predictors Of the Likelihood Of Con Rmed Lf Cases Among Ward...mentioning
confidence: 99%
“…This difference could be due to variations in occupation, exposure to rodents, or differences in immune responses. Studies have shown that males, especially farmers and hunters, are more likely to be exposed to rodents [22,23]. Genetic, hormonal, and behavioral factors may also contribute to varying susceptibility between males and females [24].…”
Section: Predictors Of the Likelihood Of Con Rmed Lf Cases Among Ward...mentioning
confidence: 99%